FRI0489 Canakinumab Improves Patient Reported Outcomes in Patients with Periodic Fever Syndromes. (15th July 2016) - Lachmann, H.; Simon, A.; Anton, J.; Gattorno, M.; Kone-Paut, I.; Ozen, S.; Frenkel, J.; Ben-Chetrit, E.; Hoffman, H.; Zeft, A.; Joubert, Y.; Lheritier, K.; et al.
Abstract : Background: Periodic Fever Syndromes (PFS) are rare autoinflammatory conditions including Familial Mediterranean Fever (FMF), Hyper-IgD Syndrome/ Mevalonate Kinase Deficiency (HIDS/MKD), and TNF-Receptor Associated Periodic Syndrome (TRAPS). 1 It has been shown that colchicine-resistant FMF (crFMF), HIDS/MKD and TRAPS considerably impact physical and emotional aspects of patients' lives. 2–4 Open label studies suggested that canakinumab (CAN), a fully human and highly specific anti-IL-1β monoclonal antibody, is efficacious in crFMF, HIDS/MKD and TRAPS. 5–7 To date, there is no data showing the effect of CAN on Health-Related Quality of Life (HRQoL) in PFS patients. Objectives: To evaluate the effect of CAN on HRQoL using Child Health Questionnaire – Parent Form 50 (CHQ-PF50) and SF-12 Health Survey (SF-12) in PFS patients. Methods: In a Phase 3 randomised placebo controlled study of CAN in PFS (NCT02059291 ), SF-12 Physical Component Summary (PCS) and Mental Component Summary (MCS) were assessed in adults. For children (>5–<18 years), CHQ-PF50 Physical (PhS) and Psychosocial (PsS) Summary scores were assessed. Results: 181 patients were randomised to CAN or placebo in 3 cohorts (63 crFMF, 72 MKD/HIDS, 46 TRAPS). 71 adults ≥18 years and 110 children (age range ≥2–<18 years). Patients reported early clinically meaningful improvement in SF-12 PCS scores reported at Week (Wk) 5 which were sustained and increased to a large effect size by Wk 16 for all indications (Table). Similarly, clinically meaningful improvements in SF-12 MCS, CHQ-PF50 PhS and PsS was observed in all indications, with the exception of PsS in HIDS/MKD and TRAPS patients (Table). Conclusions: Canakinumab showed rapid improvement by Week 5 in patient reported outcomes in adults and children with PFS, which was sustained through Week 16. References: Savic S. and Wood P. Clin. Med. 2011;11(4):396–401 Dandekar P, et al. Pediatr. Rheumatol. 13(S1):P22 Dandekar P, et al. Pediatr. Rheumatol. 13(S1):P23 Dandekar P, et al. Pediatr. Rheumatol. 13(S1):P24 Brik R, et al. Arthritis Rheumatol. 2014;66(11):3241–3 Arostegui, J.I, et al. Arthritis Rheumatol. 2015; 67 (S10) Gattorno M, et al. Arthritis Rheumatol. 2015; 67 (S10) User's manual for the SF-12v2 Health Survey, 3rd ed. 2012 Cohen J, et. al. Statistical Power Analysis for the Behavioural Sciences, 2nd ed. 1988 Disclosure of Interest: H. Lachmann Consultant for: Novartis, SOBI, Takeda, GSK, Speakers bureau: Novartis, SOBI, A. Simon Grant/research support from: CSL Behring, Novartis, Xoma/Servier, J. Anton Grant/research support from: Novartis, Pfizer, Abbvie, Roche, SOBI, Consultant for: Novartis, M. Gattorno Grant/research support from: Novartis, SOBI, Consultant for: Novartis, SOBI, Speakers bureau: Novartis, SOBI, I. Kone-Paut Grant/research support from: SOBI, Roche, Novartis, Consultant for: Novartis, SOBI, Pfizer, Abbvie, Chugai, S. Ozen Consultant for: Novartis, Speakers bureau: SOBI, J. Frenkel Grant/research support from: Novartis, SOBI, E. Ben-Chetrit Consultant for: Novartis, H. Hoffman Grant/research support from: Bristol Myers Squibb, Consultant for: Novartis, Sob Biovitrum, Regeneron, Speakers bureau: Novartis, A. Zeft: None declared, Y. Joubert Employee of: Novartis, K. Lheritier Employee of: Novartis, A. Speziale: None declared, G. Junge Employee of: Novartis, J. Gregson Employee of: Novartis, F. De Benedetti Grant/research support from: Pfizer, Abbvie, Roche, Novartis, Novimmune, BMS